Current status of the application of digital impression technology in removable partial dentures - WANG Youjin, WEI Bin (Editorial Office of Stomatology, 2024)
Removable partial denture is one of the most important means of treating dental defects for its high strength, low price, wide range of indications, minimal trauma and repairability. With the aging of the population becoming more and more prominent, removable partial dentures will continue to be a common restorative method in the future. The production of removable partial denture cannot be separated from the accurate impression technology, and there are many shortcomings in the process of taking impressions of traditional removable partial denture, such as the number of visits, time-consuming, complex production process, high pollution, waste, low efficiency, and the quality is not easy to control, etc. However, the emergence of digital impression provides new technical support for the taking of removable partial denture impression. Digital impression technology has the advantages of high precision, comfort, high efficiency, shortened treatment time and personalized design, which helps to improve the effect of removable partial denture restoration and patient satisfaction. As the premise and foundation of the whole digital removable partial denture restoration treatment, accuracy of the reconstruction of the oral model directly affects the final denture restoration effect. At present, digital impression technology has been widely used in the field of oral restoration. This paper will review the current status of the application of digital impression technology in removable partial denture, in order to further guide the clinical application.